Volume 1B: 36th Computers and Information in Engineering Conference 2016
DOI: 10.1115/detc2016-59964
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Manufacturing Ontology for Functionally Graded Materials

Abstract: The development of manufacturing technologies for new materials involves the generation of a large and continually evolving volume of information. The analysis, integration and management of such large volumes of data, typically stored in multiple independently developed databases, creates significant challenges for practitioners. There is a critical need especially for open-sharing of data pertaining to engineering design which together with effective decision support tools can enable innovation.We believe th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 23 publications
0
8
0
Order By: Relevance
“…Responding to a call for proposals from the Digital Manufacturing and Design Innovation Institute (DMDII) CUBRC and the University at Buffalo initiated the Coordinated Holistic Alignment of Manufacturing Process (CHAMP) project [31] with the goal of creating a flexible suite of interoperable generic public-domain ontologies covering the design, manufacturing, testing process, maintenance and tool domains. Through the CHAMP project, the Product Life Cycle Ontologies were created, and the FGMO 2.0, a revision of the FGMO [2] (named as FGMO 1.0 after this point onward) was developed as potential contribution to the IOF framework.…”
Section: Examples Of Bfo-based Engineering Ontologies Include the Commentioning
confidence: 99%
See 2 more Smart Citations
“…Responding to a call for proposals from the Digital Manufacturing and Design Innovation Institute (DMDII) CUBRC and the University at Buffalo initiated the Coordinated Holistic Alignment of Manufacturing Process (CHAMP) project [31] with the goal of creating a flexible suite of interoperable generic public-domain ontologies covering the design, manufacturing, testing process, maintenance and tool domains. Through the CHAMP project, the Product Life Cycle Ontologies were created, and the FGMO 2.0, a revision of the FGMO [2] (named as FGMO 1.0 after this point onward) was developed as potential contribution to the IOF framework.…”
Section: Examples Of Bfo-based Engineering Ontologies Include the Commentioning
confidence: 99%
“…The mid-level is modeled on the Ontology for Biomedical Investigations (OBI) [35]. Furini et al [2] detail the FGMO 1.0, which covers FGM research in the area of components, manufacturing processes, material properties, and applications, focusing on the domain level to include low-level classes related to directly to FGM research [36] [37] [38].…”
Section: Fgmo 10 Ontology Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…17 One early example of the use of BFO in the industrial domain is provided by the OBO Ontology for Biomedical Investigations, the idea for which was first sketched by Whetzel, (2006), and more specifically in the OBI Materials Transformation branch, which deals with inputs and outputs of processes such as blending, mixing, staining, and so forth (Bandrowski et al 2016). This part of OBI was used in the development of an ontology for functionally graded materials (Furini et al 2016).…”
Section: Relations In Product Life Cycle Ontologiesmentioning
confidence: 99%
“…The expectations of the IOF is to enable similar opportunities for the engineering community. Interested readers can refer to initial work from Furini et al [192] that provides a BFO-based ontology for functionally graded materials. Structured taxonomic representations, such as those presented by Kumaraguru et al [193], also expedite the prototyping of visual representations, as shown by Li and Bernstein [194].…”
Section: Future Research Directionsmentioning
confidence: 99%